Interprofessional strengths and weaknesses in the care of people with ostomies: a mixed-methods study - Jorge Silva Correa Júnior, Antonio; Prates, Pedro Emílio Gomes; Santana, Mary Elizabeth de; Lima, Fernando Conceição de; Teles, André Aparecido da Silva; Sonobe, Helena Megumi (Estima – Brazilian Journal of Enterostomal Therapy, 2025)
Objective: To analyze the activities of a secondary care team specialized in assisting individuals with elimination stomas, interpreting the distances and proximities with interprofessionality. Method: A mixed-method study conducted in a service for people with stomas in northern Brazil, involving 16 professionals. The descriptive qualitative phase was based on Émile Durkheim’s Social Facts, and utilized semi-structured interviews and field notes with reflective thematic analysis. The quantitative phase used a questionnaire survey designed by experts and descriptive percentage analysis. Results: A total of 31 activities were described, with low expressiveness of those that foster interprofessionality, such as reception, checking family dynamics, education in the waiting room, active search for vulnerable patients’ records, scheduling follow-up with social services, reviewing family dynamics, and addressing patients’ rights. Two topics were developed: (1) Operational aspects of (search for) interprofessionality: registration, management, active search, and referrals; and (2) Acquiring autonomy for social reintegration and moving away from self-care: collaborative elements in the journey from beginning to “restart”. Conclusion: Interprofessionality remains a distant work model; however, collaborative practices have begun to emerge through referrals. Emphasis on intersectionality and intersectorality is crucial to support the social reintegration of patients.